Total urgency and frequency score as a measure of urgency and frequency in overactive bladder and storage lower urinary tract symptoms. (20th February 2014) - Chapple, Christopher R.; Drake, Marcus J.; Van Kerrebroeck, Philip; Cardozo, Linda; Drogendijk, Ted; Klaver, Monique; Van Charldorp, Karin; Hakimi, Zalmai; Compion, Gerhard
Abstract : The term lower urinary tract symptoms (LUTS) encompasses a range of urinary symptoms, including storage symptoms (e.g. overactive bladder [OAB]) as well as voiding and post‐micturition symptoms. Although treatment of male LUTS tends to focus on voiding symptoms, patients typically find storage symptoms the most bothersome. The core storage symptom is urgency, which drives the other main storage symptoms of increased daytime frequency, nocturia and incontinence. Although several validated questionnaires have been widely used to study urgency, few measure the two important storage parameters, urgency and frequency, in a single assessment. The total urgency and frequency score (TUFS) is a new validated tool that captures both variables and is derived from the Patient Perception of Intensity of Urgency Scale, which has been validated in patients with OAB and LUTS. The TUFS was first validated in OAB in the phase IIa BLOSSOM study, which was designed to assess the efficacy and safety of mirabegron, a β3 ‐adrenoceptor agonist, in 260 patients. The responsiveness of the TUFS to treatment has been confirmed in a further three large‐scale randomized controlled trials of solifenacin in patients with OAB or LUTS. Changes in TUFS from baseline to end of treatment were consistent with changes in micturition diary variables in all four studies. Furthermore, the TUFS was significantly correlated with several health‐related quality‐of‐life variables in the phase III NEPTUNE study. Thus, the TUFS appears to be useful for assessing improvements in major storage symptoms (urgency and frequency) in clinical trials.